Murder after death: literature and anatomy in early modern England - Sugg, Richard (Cornell University Press, 2007)
Between the skin and the bone : anatomy, violence, and transition -- "I'll eat the rest of th'anatomy" : dissection and cannibalism -- The body as proof -- The split body -- Vivisection, violence, and identity